Botany, traditional uses, phytochemistry, pharmacology, toxicology and processing of Rhizoma alismatis: a review - Pan, Tianhan; Tang, Ruonan; Wang, Jiawen; Gao, Jia; Jiang, Fusheng; Chen, Buyang (Frontiers in Pharmacology, 2025)
BackgroundRhizoma alismatis is a traditional Chinese medicine with a long history. It is an important part of many prescriptions and is often used to treat water metabolism-related diseases in clinical practice. At present, there are 12 species of R. alismatis, of which only Alisma plantago-aquatica L. and A. plantago-aquatica subsp. orientale (Sam.) Sam are used as traditional Chinese medicine.ObjectiveBased on the scientific literature, this paper aims to provide comprehensive and up-to-date information on the botany, traditional uses, phytochemistry, pharmacology, toxicology and processing methods of R. alismatis. Furthermore, it seeks to analyze current research findings to establish a new foundation and direction for future studies.MethodsMultidisciplinary research domains including botanical identification, ethnopharmacological applications, phytochemical constituents, pharmacological activities, toxicological profiles, and processing techniques, drawing upon extensive data retrieved from PubMed, Web of science, CNKI, and other authoritative databases.ResultsTraditional Chinese medicine believes that R. alismatis has the effects of promoting water and dampness and venting heat. Modern studies have found that its extracts and isolated compounds have diuretic, liver protection, lowering blood pressure, lowering blood glucose, anti-cancer, anti-inflammatory and antioxidant activities. The toxicity of R. alismatis has long been a controversial topic, and it is generally held that no obvious adverse reactions occur within the prescribed dosage range.ConclusionModern studies partially explains the traditional concept of R. alismatis’ functions and the corresponding pharmacodynamic material basis. It is necessary to further study the network relationship between traditional usage, modern pharmacology and toxicity, and standardize the cultivation, processing and circulation system of R. alismatis.